An investigation of the causality links in the balanced scorecard: The case of the Gulf Cooperation Council hospitality industry. (January 2022) - Elbanna, Said; Kamel, Hany; Fatima, Tahniyath; Eid, Riyad
Abstract: In order to link different aspects of the balanced scorecard (BSC), i.e., learning, innovation, internal business, customer, and financial perspectives, Kaplan and Norton developed the concept of strategy maps to help managers recognize how improvement in one perspective would affect the other perspectives and ultimately improve financial results. Despite its importance and the fact that the BSC has been studied extensively over the last three decades, the concept of causality among BSC perspectives is not adequately explained and remains ambiguous. To fill this research gap, we collected data from 175 five- and four-star hotels located in two Gulf Cooperation Council countries (GCC), namely, the United Arab Emirates (UAE) and Qatar, and examined the causal links among the overall perspectives of the BSC framework. Our path analysis results provide empirical support to the traditional cause-and-effect relationships in the BSC and portrays new findings pertaining to segregation of innovation and learning perspectives and the presence of indirect relationships between learning and customer perspectives. Highlights: Balanced scorecard in the GCC hotel industry is semi-hierarchical in nature Innovation and learning perspectives are treated as two stand-alone perspectives Learning perspective forms the foundational perspective of the balanced scorecard Balanced scorecard is both a metric to assess performance and a system to manage strategy